Gamifier les évalutions en classe - Kutasevych, Halyna; Yakubovska, Nataliia O. (Чернівці–Сучава: БДМУ, 2021)
The relevance of the research is justified by the need to study the relationship between motivation and assessment as key spects of learning French. This interdependence presupposes the search for the latest approaches to assessment, that apart from aiming at the final outcome of learning, are also focused on the student’s development (progress). From that perspective it is particular importance to resort to gamification that provides for applying game mechanics to non-game contexts. This approach has recently become a widely-held across a wide range of industries demonstrating its potential in education. The main purpose of the scientific research is to highlight the main aspects of gamified assessment in French-as-a-foreign- language lessons. The scientific novelty of the paper is defined by in the fact that for the first time it outlined the main mechanisms of gamification as assessment tool. The author applied the method of critical analysis of the scientific sources and the method of scientific observation of the pedagogical process. Conclusions. Gamification in the context of assessment involves introducing game elements in order to make it more approachable and thereby to assure students’ engagement and motivation when conducting the assessment. Gamification as a tool can be applied to the design of innovative tasks related to assessment. It is argued that the inclusion of some aspects of the gamification technology can have a positive effect on the development of innovative assessment system. However, reasonable combination of such technologies with already existing teaching methods can be viewed as a guarantee of students’ effective formation of French competence in the process of foreign language learning.
Гейміфікація оцінювання на уроках французької мови
Keywords: gamification; evaluation; motivation; electronic means; foreign language competence